High-intensity focused ultrasound ablation in the treatment of fumarate hydratase-deficient uterine leiomyoma - Luyao Zhang; Zhouzhou Liao; Jianfa Jiang (International Journal of Hyperthermia)
Objective This study aimed to explore the efficacy and safety of high-intensity focused ultrasound (HIFU) ablation for treating fumarate hydratase (FH)-deficient uterine leiomyomas.Method Ten patients with FH-deficient uterine leiomyomas treated with HIFU ablation at the Third Xiangya Hospital from July 2017 to January 2023 were enrolled in this study. The effectiveness and adverse effects of HIFU were analyzed.Results The median age of the patients who received HIFU was 32.0 years (range: 28–41 years). Only 2 patients had solitary uterine leiomyomas, whereas the remaining 8 patients had multiple uterine leiomyomas. The median diameter of the largest myoma was 56 mm (range: 41–99 mm). Magnetic resonance imaging showed that the FH-deficient uterine leiomyomas of 8 patients presented as mixed intensity on T2WI, that of one patient was hypointense, and that of another patient was hyperintense on T2WI. All patients successfully underwent HIFU ablation in one session without severe adverse effects. The median nonperfusion volume ratio (NPVR) was 40% (30.0%–78.0%) after HIFU treatment. Four patients had NPVR ≥70%. At 3-month follow-up after HIFU ablation, the clinical symptoms of 5 of the 8 patients with symptoms before treatment were relieved. Six months after treatment, 4 of the 8 patients with symptoms were still in remission. All patients received reintervention by March 2024. The reintervention rates were 20%, 70%, and 90% at 12, 24, and 36 months, respectively, after HIFU ablation.Conclusion HIFU is a safe and feasible treatment for FH-deficient uterine leiomyomas, and most patients show effective results in the short term after treatment. However, the reintervention rates are high, and the long-term effects are limited.